USE OF SYNONYMY AND VARIATION IN LITERARY TRANSLATION - Botirova Sojida Jomurodovna (Journal Park Publishing, 2024)
The art of literary translation is a nuanced endeavor where the translator faces the challenge of faithfully capturing the essence of a source text while accommodating the complexities of the target language. This article delves into the dynamic use of synonymy and variation in literary translation. It examines how translators navigate the intricate terrain of synonyms and variations to convey the richness of the source text, maintain its literary style, and resonate with the target audience. Through a comprehensive analysis of case studies and translation theories, this article sheds light on the creative strategies and linguistic choices employed by translators to strike a delicate balance between fidelity and creativity in the realm of literary translation.
Keywords: Literary translation, Synonymy, Variation, Fidelity, Creative translation, Target audience, Source text, Translation strategies, Linguistic choices, Translational creativity.